2022
DOI: 10.12785/ijcds/110143
|View full text |Cite
|
Sign up to set email alerts
|

A Real-time Machine Learning-Based Person Recognition System With Ear Biometrics

Abstract: Biometric authentication is a common way of granting access to a system or device. The ear, like fingerprints, retina, iris, face, voice, and so on, is a biometric modality. Compared to other biometric organs, the anatomy of a human's ear remains stable from birth to old life. As a visible organ with an easily acquired image, it may also be a source of a biometric signature that may be used to identify individuals. This research demonstrates two approaches to recognizing a person from 2D ear images: non-deep M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For ear detection and ear identification tasks, Faster-RCNN and VGG-19 are employed [37]. Recently, Shamim Akhter et al [19], [20] used the YOLOV3 model with a standard dataset named EarVN1.0. This collection was made up of 28412 ear pictures from 164 different groups.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For ear detection and ear identification tasks, Faster-RCNN and VGG-19 are employed [37]. Recently, Shamim Akhter et al [19], [20] used the YOLOV3 model with a standard dataset named EarVN1.0. This collection was made up of 28412 ear pictures from 164 different groups.…”
Section: Related Workmentioning
confidence: 99%
“…The studies from [25], [26], [27], [28], [29] and [31] showed ML models for recognizing and identifying the ear from image data sets. However, [19], [20], [32], [37] studies use ear images to identify individuals. A typical classification issue requires the detection and localization of objects.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…YOLO version one (YOLOv1) [37] as its neck in order to enhance information flow. With an enhanced bottom-up strategy, PA-Net leverages a unique feature pyramid network (FPN) design to improve the transmission of low-level features.…”
Section: B Yolov5 Deep Network Modelmentioning
confidence: 99%
“…The commonly used biometric traits like voice, fingerprints, iris, face recognition, and palmprint necessitates the enrolment of such traits in databases for feature detection [3][4][5]. The biometric system acts as a auspicious and continuously developing technology utilized in the automatic systems for finding an individual effectively without remembering or carrying anything, such as passwords and Ids [6][7][8][9]. Numerous research works that the iris trait has higher advantages compared to other biometric systems relevant to the features such as fingerprint and face, this makes the iris to be generally adopted in several applications for high-reliability and precise biometric systems [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%